Training on Stormwater Management. Training Manual. A Training Course for Decision Makers and Operative Staff from ULB Level. - (:unkn) unknown (Neu-Dehli, 2022)
The manual is designed for the training of operative staff in the field of water management and water infrastructure, including storm water management, as well as decision makers at Urban Local Body (ULB) level. The methodology of the training sessions focuses on practice-oriented and interactive learning. They help to reflect the content and, whenever possible, deepen the learnings. After the training, participants will be able to independently perform some of the analyses required for the CSCAF and have all required information to tender out more detailed assessments where necessary. The sessions are divided into sections. Each section starts with a general description and background information, exercises follow that reflect the content to increase the participants’ knowledge and experience. Instructions on how to move from planning to implementation are described subsequently.
Keywords: Indien; Regenwassermanagement; Handbuch; Trainingsprogramm; Stadtentwicklung; Infrastrukturentwicklung; Nachhaltige Entwicklung